1982
DOI: 10.1289/ehp.8246111
|View full text |Cite
|
Sign up to set email alerts
|

Organic N-chloramines: chemistry and toxicology.

Abstract: The stability of aqueous solutions of organic N-chloramines, suspected of contaminating chlorinated water, has been studied. Two factors influence the decomposition of solutions of N-chloropiperidine and N-chlorodiethylamine: a spontaneous decomposition and photodecomposition. Since solutions of these compounds are relatively long-lived, a need for an analytical method for their identification is discussed. A new method is described which involves reaction of organic N-chloramines with arenesulfinic acid salts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…3). Hydrolysis rates of HANs increase with pH [85,86]. There is limited data about haloacetamides in drinking water, although dichloroacetamide (DCAcAm) occurred at comparable levels to the equivalent haloacetonitrile (DCAN) in the US 2000-2002 survey: respective median concentrations were 1.4 and 1.0 g L −1 (Table 4), which is consistent with the hydrolysis route outlined above.…”
Section: Haloacetamides (Hacams) and Their Precursorssupporting
confidence: 65%
See 1 more Smart Citation
“…3). Hydrolysis rates of HANs increase with pH [85,86]. There is limited data about haloacetamides in drinking water, although dichloroacetamide (DCAcAm) occurred at comparable levels to the equivalent haloacetonitrile (DCAN) in the US 2000-2002 survey: respective median concentrations were 1.4 and 1.0 g L −1 (Table 4), which is consistent with the hydrolysis route outlined above.…”
Section: Haloacetamides (Hacams) and Their Precursorssupporting
confidence: 65%
“…2 and 3 that the first step of either amino acid chlorination route is the formation of an organic n-chloramine. Such species are expected to form rapidly and quantitatively by aqueous reactions between model amines and chlorine [86] and are therefore likely to be important DBPs in their own right. Work chlorinating bulk DON also showed organic chloramines formed rapidly (within 10 min), whereas formation following chloramination was much slower (from 2 to 120 h) [87].…”
Section: Haloacetonitriles (Hans) and Their Precursorsmentioning
confidence: 99%
“…In other research endeavors, N-chloroglycine was formed as a result of the reaction of monochloramine with glytine under conditions typical for drinking water,z2 and it has been suggested that CNCl is formed by the reaction of glycine with chlorine.= Studies have demonstrated the formation of organochloramines by the use of inorganic chloramines in the treatment of water. 24 The CNCl results presented here, as well as the presence of moderate concentrations of TOX in chloraminated waters with low THM levels, indicate a need to further identify chloramine by-products. Aldehydes.…”
Section: Imentioning
confidence: 72%
“…Furthermore, wastewater-derived DON affects the efficiency of chlorination and dechlorination processes. When chlorine reacts with DON, especially with primary and secondary amines, organic chloramines form (Scully and Bempong, 1982;Fleischacker and Randtke, 1983;Scully et al, 1988a;Rebhun et al, 1997), and many of these species do not have germicidal properties, although standard chlorine residual tests, such as the DPD colorimetric assay (APHA, 1998), do not discriminate between organic and inorganic chloramines and measure them as combined residual chlorine (Jensen and Johnson, 1990). Therefore, the total residual chlorine measurement is not appropriate for assessment of disinfection in wastewater that contains relatively high concentrations of DON.…”
Section: Effects Of Wastewater-derived Donmentioning
confidence: 99%